2019
DOI: 10.1177/0265407519884726
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the effects of partner responsiveness on health and well-being: The role of perceived control

Abstract: Perceived partner responsiveness (PPR)—the extent to which people feel understood, cared for, and appreciated—has been identified as an organizing principle in the study of close relationships. Previous work indicates that PPR may benefit physical health and well-being, but how PPR is associated with personal benefits is less clear. One cognitive mechanism that may help to explain these associations is perceived control. Here we tested two competing models (moderation vs. mediation) in which we assessed whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
3
18
0
2
Order By: Relevance
“…Our overall findings not only support the main effects of perceived control on perceived health and life satisfaction but also demonstrate its buffering effect on adjusting psychological outcomes among people living in pandemic‐affected regions (Alonso‐Ferres et al, 2020; Lachman, 2006).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our overall findings not only support the main effects of perceived control on perceived health and life satisfaction but also demonstrate its buffering effect on adjusting psychological outcomes among people living in pandemic‐affected regions (Alonso‐Ferres et al, 2020; Lachman, 2006).…”
Section: Discussionsupporting
confidence: 74%
“…According to the present study’s findings, perceived control can serve as a protective factor against the psychological effects of COVID‐19. In particular, perceived control was found to enhance the participants’ capacity to deal with stressors and alter the subjective experience of environmental stressors (Alonso‐Ferres et al, 2020; Lachman, 2006; Li, Yang, Dou, & Cheung, 2020). This study found that perceived control could moderate the mediating effect of psychological distance, in which perceived control not only buffers the detrimental effects of regional pandemic severity on psychological distance, but also alleviates the negative impact of psychological distance from COVID‐19 on perceived life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…As perceived control acts as a protective factor against the psychological effects of COVID-19, there are studies in literature reporting that perceived control increases participants' ability to cope with stressors and changes the subjective experience of environmental stressors. [15,31,32] According to findings of the present study, in the macro control subdimension of the COVID-19 Perceived Control Scale, any increase in the fear of COVID-19 created a slight decrease in the perceived control of COVID-19. However, any increase in the fear of COVID-19 resulted in a slight increase in the personal control and inevitability subdimensions of FCV-19S (Table 3).…”
Section: Discussionsupporting
confidence: 62%
“…These findings of the present study partially support the literature findings. [15,31,32] Despite these findings, when the relationship between FCV-19S and CV-19PCS total scores was evaluated, no correlation was found between the fear of COVID-19 and the perceived control of COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…1 问题提出 控制感是一种心理资源, 是个体心理健康的重 要变量 (Infurna et al, 2011;Ruthig et al, 2007)。增 强控制感不仅能够提高人的自我效能感和幸福感, 改善应对方式 (Alonso-Ferres et al, 2019;Drewelies et al, 2018), 使人更好地适应社会环境 (Zhou et al, 2012), 还能够改善对灾害等负面事物的心理距离 感知 (Han et al, 2018), 提高健康水平和生活满意 度 (Alonso-Ferres et al, 2019;Drewelies et al, 2018;Zheng et al, 2020)。控制感增强还能够降低人的攻 击行为和反社会行为 (Warburton et al, 2006)…”
unclassified